2015
DOI: 10.2139/ssrn.2656040
|View full text |Cite
|
Sign up to set email alerts
|

Sense and No(n)-Sense of Energy Security Indicators

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Based on the data presented in Figures 1 and 2, it can be seen that there is a relationship between income and the level of energy consumption, thus it was shown that in both 2010 and 2020 there was a phenomenon that the higher the income per person, the higher the electricity consumption. Net Import Dependency ratio (NID) [9]:…”
Section: Characteristics Of the Energy Security Indicatorsmentioning
confidence: 99%
“…Based on the data presented in Figures 1 and 2, it can be seen that there is a relationship between income and the level of energy consumption, thus it was shown that in both 2010 and 2020 there was a phenomenon that the higher the income per person, the higher the electricity consumption. Net Import Dependency ratio (NID) [9]:…”
Section: Characteristics Of the Energy Security Indicatorsmentioning
confidence: 99%
“…The dimensions range from the sustainability and environmental impacts of energy production to the security of supply and energy system costs [8]. No academic consensus has been reached in the definitions or indicators that should be used for political decision-making [9]. As one important authority, the International Energy Association defines energy security as the uninterrupted availability of energy sources at an affordable price [10].…”
Section: Relevant Dimensions Of Energy Securitymentioning
confidence: 99%
“…Je abstrahován široký komplex energetické bezpečnosti a pro zjednodušení rovněž různá tržní i netržní rizika potenciálně komplikující výpočty indexů. Pokus o indexaci energetické bezpečnosti v komplexním pojetí zahrnující politický, ekonomický, sociální a ekologický rozměr je velmi obtížný a jeho vypovídací hodnota může být zpochybňována (Böhringer -Bortolamedi 2015).…”
unclassified